Analysis of Factors Influencing Foreign Direct Investment Entry in G-20 Member Countries: Empirical Study of Developing and Developed Countries 2015-2019 - Dewi, Ni Putu Intan Febriani; Setyari, Ni Putu Wiwin (CV. Rayyan Dwi Bharata, 2025)
Foreign Direct Investment (FDI) is an important element in the global economic system that plays a significant role in strengthening the foundations of a country's economic growth. However, based on data on FDI flows between the G-20 countries, there is an imbalance that requires further study. The study aims to analyze the impact of GDP, EODB Scores, real interest rates and country classifications both simultaneously and partially on FDI in G-20 member states in 2015-2019. The method of analysis used in this study was double linear regression with an GLS model as well as inserting one dummy variable with STATA software version 14. The results showed that simultaneously variables of GDP, EODB Scores, Real Interest Rates and Country Classifications have a significant influence on G20 member countries' Foreign Direct Investment. Meanwhile, partially GDP has a positive and significant influency on FDI while EODb Scores and Real Interests and Country Classes have a positive but non-significant influence over FDI.